Ätiologische Konzepte von gastrointestinalen Fehlbildungen/Atresien - Reutter, Heiko Martin (Monatsschrift Kinderheilkunde, 2023)
The causes of gastrointestinal malformations or atresias are heterogeneous. Most atresias occur sporadically. To date, no environmental factor or genetic defect has been identified that alone could causally explain a large proportion of the various malformations. Due to the capabilities of modern array and exome analyses, numerous new disease genes have been identified in the past 10 years. It is known that a small overlap of individual causative genetic risk factors underlies the co-occurrence of malformations of the esophagus and anorectum, and that a large proportion of duodenal atresias occur in the context of an underlying Down syndrome; however, for the vast majority of intestinal atresias the genetic causes remain unclear. The human genetic counselling should consider epidemiological aspects of the observed recurrence risk for the different atresias and the appearance of each atresia (syndromic or non-syndromic, isolated).
CRIS-Team Scopus Importer:2023-05-19
Keywords: Chromosome disorders; DNA copy number variations; Epidemiology; Pathogenesis; Recurrence risk